1989
DOI: 10.1152/jappl.1989.67.3.959
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 causes accumulation of eosinophils in the lumen of the dog trachea

Abstract: Prostaglandin D2 (PGD2), the major product of arachidonic acid metabolism via the cyclooxygenase pathway in most mast cells, is present in the airways of atopic asthmatic patients after antigen challenge. Because eosinophilia is characteristic of asthma, we asked whether PGD2 causes eosinophils to accumulate in the airways in vivo. Using an endotracheal tube with two inflatable balloons we isolated a segment of trachea in four anesthetized mechanically ventilated dogs, and we superfused this segment with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 0 publications
3
36
2
Order By: Relevance
“…14 Furthermore, in dogs, PGD 2 caused a rapid reduction in circulating eosinophil levels, 15 whereas tracheal superfusion of PGD 2 in vivo induced the recruitment of eosinophils but not neutrophils into the superfusate. 16 It is unclear from the above studies whether the in vivo effects of PGD 2 are due to direct effects on eosinophils or are caused by the release of mediators from other cells. However, PGD 2 has been reported to directly stimulate calcium mobilization and LTC 4 release in vitro in human eosinophils.…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, in dogs, PGD 2 caused a rapid reduction in circulating eosinophil levels, 15 whereas tracheal superfusion of PGD 2 in vivo induced the recruitment of eosinophils but not neutrophils into the superfusate. 16 It is unclear from the above studies whether the in vivo effects of PGD 2 are due to direct effects on eosinophils or are caused by the release of mediators from other cells. However, PGD 2 has been reported to directly stimulate calcium mobilization and LTC 4 release in vitro in human eosinophils.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that PGD 2 , a major cyclooxygenase (COX) 3 metabolite synthesized in activated mast cells and macrophages, is released during early and late asthmatic responses following allergen exposure (13,14), and acts as a potent chemoattractant of eosinophils in vitro (15,16) and in vivo (17,18). We have reported that COX-2 inhibitors, which stop the synthesis of PGD 2 in the lungs of allergen-sensitized and exposed guinea pigs, attenuated the accumulation of eosinophil in the airways (19).…”
mentioning
confidence: 99%
“…PGD 2 binds to and activates two G-protein-coupled receptors, DP1 and CRTH2 (chemoattractant receptor-homologous molecule expressed on Th type 2 cells), also known as DP2. Within the immune system, DP1 activation regulates human and murine dendritic cell migration (9), whereas CRTH2͞DP2 is expressed on type 2 lymphocytes (10), eosinophils (11), and basophils (12), where it mediates eosinophil chemotaxis and is currently implicated as a central player in promoting Th2-related allergic inflammation (13). Although 15d-PGJ 2 was identified as a high-affinity natural ligand for peroxisome proliferator-activated receptor (PPAR)␄, it is now thought to exert its effects through PPAR␄-dependent and -independent mechanisms, resulting in the suppression of various proinflammatory signaling pathways (2).…”
mentioning
confidence: 99%